2017
DOI: 10.1016/j.arthro.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anterolateral Ligament Length Change in the Healthy Knee During Functional Activities—A Combined Magnetic Resonance and Dual Fluoroscopic Imaging Analysis

Abstract: Purpose To measure the in vivo anterolateral ligament (ALL) length change in healthy knees during step-up and sit-to-stand motions. Methods Eighteen healthy knees were imaged using magnetic resonance (MR) and dual fluoroscopic imaging techniques during a step-up and sit-to-stand motion. The ALL length change was measured, using the shortest 3-D wrapping path, with its femoral attachment located slightly anterior-distal (ALLClaes) or posterior-proximal (ALL-Kennedy) to the fibular collateral ligament (FCL) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 32 publications
3
29
0
4
Order By: Relevance
“…In addition, similar to Kernkamp et al (2017), we denoted that LER lengthened during the early degrees of knee flexion and started to shorten at about 35 degrees of knee flexion when the femoral graft was located posteriorly and proximally to the femoral epicondyle and the tibial graft positioned on the gerdys's tubercle or anatomical insertion of the anterolateral ligament ( Supplementary File 2). In addition, previous cadaveric studies (Geeslin et al, 2018;Inderhaug et al, 2017aInderhaug et al, , 2017b pointed out that LER controlled knee rotation and anterior translation.…”
Section: Evaluation Of Model Outputssupporting
confidence: 59%
“…In addition, similar to Kernkamp et al (2017), we denoted that LER lengthened during the early degrees of knee flexion and started to shorten at about 35 degrees of knee flexion when the femoral graft was located posteriorly and proximally to the femoral epicondyle and the tibial graft positioned on the gerdys's tubercle or anatomical insertion of the anterolateral ligament ( Supplementary File 2). In addition, previous cadaveric studies (Geeslin et al, 2018;Inderhaug et al, 2017aInderhaug et al, , 2017b pointed out that LER controlled knee rotation and anterior translation.…”
Section: Evaluation Of Model Outputssupporting
confidence: 59%
“…However, cadaveric studies is limited as the in‐vitro testing condition cannot properly simulate in‐vivo physiological knee performances . In this study, the ACL and PCL length measurement under in‐vivo conditions was performed using a previously published technique . The ACL and PCL attachment areas on the BCR TKA and non‐operated knees were first determined at each flexion angle.…”
Section: Methodsmentioning
confidence: 99%
“…The ACL and PCL attachment areas on the BCR TKA and non‐operated knees were first determined at each flexion angle. An optimization procedure was implemented to find the shortest 3D wrapping path of each bundle of ACL and PCL portion during STS, and the lengths of each portion were determined . Following that, determination of the wrapping length (ɭ) of each bundle of ACL and PCL during STS was performed.…”
Section: Methodsmentioning
confidence: 99%
“…These should be located such that the LER confers physiological knee kinematics, specifically restoration of rotational control and avoidance of overconstraint [10]. The recent literature, including in-vivo and in-vitro studies, has reported a range of different femoral tunnel positions which includes directly proximal to the lateral epicondyle [9-11-12], posteroproximal [13][14] or postero-distal [15]. However, there is increasing consensus that a posteroproximal femoral attachment allows the most favorable behavior, with an LER that is lengthened in knee extension and shortened in flexion [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature, including in-vivo and in-vitro studies, has reported a range of different femoral tunnel positions which includes directly proximal to the lateral epicondyle [9-11-12], posteroproximal [13][14] or postero-distal [15]. However, there is increasing consensus that a posteroproximal femoral attachment allows the most favorable behavior, with an LER that is lengthened in knee extension and shortened in flexion [10][11][12][13][14][15]. With respect to the tibial graft insertion, Wieser, Furnstahl, Carrillo, Fucentese and Vlachopoulos [12] reported that, during a weight-bearing squat, the most isometric point was located at 37% of the postero-anterior width of the tibial plateau.…”
Section: Introductionmentioning
confidence: 99%